IFN-gamma signaling maintains skin pigmentation homeostasis through regulation of melanosome maturation - Natarajan, Vivek T.; Ganju, Parul; Singh, Archana; Vijayan, Vinaya; Kirty, Kritika; Yadav, Shalini; Puntambekar, Shraddha; Bajaj, Sonali; Dani, Prachi P.; Kar, Hemanta K.; Gadgil, Chetan J.; Natarajan, Krishnamurthy; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Cellular homeostasis is an outcome of complex interacting processes with nonlinear feedbacks that can span distinct spatial and temporal dimensions. Skin tanning is one such dynamic response that maintains genome integrity of epidermal cells. Although pathways underlying hyperpigmentation cascade are recognized, negative feedback regulatory loops that can dampen the activated melanogenesis process are not completely understood. In this study, we delineate a regulatory role of IFN-gamma in skin pigmentation biology. We show that IFN-gamma signaling impedes maturation of the key organelle melanosome by concerted regulation of several pigmentation genes. Withdrawal of IFN-gamma signal spontaneously restores normal cellular programming. This effect in melanocytes is mediated by IFN regulatory factor-1 and is not dependent on the central regulator microphthalmia-associated transcription factor. Chronic IFN-gamma signaling shows a clear hypopigmentation phenotype in both mouse and human skin. Interestingly, IFN-gamma KO mice display a delayed recovery response to restore basal state of epidermal pigmentation after UV-induced tanning. Together, our studies delineate a new spatiotemporal role of the IFN-gamma signaling network in skin pigmentation homeostasis, which could have implications in various cutaneous depigmentary and malignant disorders.
Keywords: detanning; gene regulation; interferon; melanin

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.

Chronic systemic exposure to IL6 leads to deregulation of glycolysis and fat accumulation in the zebrafish liver - Singh, Manoj K.; Jayarajan, Rijith; Varshney, Swati; Upadrasta, Sindhuri; Singh, Archana; Yadav, Rajni; Scaria, Vinod; Sengupta, Shantanu; Shanmugam, Dhanasekaran; Shalimar; Sivasubbu, Sridhar; Gandotra, Sheetal; et al. (Biochimica ET Biophysica Acta-Molecular and Cell Biology of Lipids, 2021)
Inflammation is a constant in Non-Alcoholic Fatty Liver Disease (NAFLD), although their relationship is unclear. In a transgenic zebrafish system with chronic systemic overexpression of human IL6 (IL6-OE) we show that inflammation can cause intra-hepatic accumulation of triglycerides. Transcriptomics and proteomics analysis of the IL6-OE liver revealed a deregulation of glycolysis/gluconeogenesis pathway, especially a striking down regulation of the glycolytic enzyme aldolase b. Metabolomics analysis by mass spectrometry showed accumulation of hexose monophosphates and their derivatives, which can act as precursors for triglyceride synthesis. Our results suggest that IL6-driven repression of glycolysis/gluconeogenesis, specifically aldolase b, may be a novel mechanism for fatty liver. This mechanism may be relevant for NAFLD in lean individuals, an emerging class of NAFLD prevalent more in Asian Indian populations.
Keywords: Aldolase b; DHAP; Inflammation; Interleukin 6; Lean NAFLD; Non-alcoholic fatty liver

Temporal analysis of melanogenesis identifies fatty acid metabolism as key skin pigment regulator - Sultan, Farina; Basu, Reelina; Murthy, Divya; Kochar, Manisha; Attri, Kuldeep S.; Aggarwal, Ayush; Kumari, Pooja; Dnyane, Pooja; Tanwar, Jyoti; Motiani, Rajender K.; Singh, Archana; Gadgil, Chetan; et al. (Plos Biology, 2022)
Therapeutic methods to modulate skin pigmentation has important implications for skin cancer prevention and for treating cutaneous hyperpigmentary conditions. Towards defining new potential targets, we followed temporal dynamics of melanogenesis using a cell-autonomous pigmentation model. Our study elucidates 3 dominant phases of synchronized metabolic and transcriptional reprogramming. The melanogenic trigger is associated with high MITF levels along with rapid uptake of glucose. The transition to pigmented state is accompanied by increased glucose channelisation to anabolic pathways that support melanosome biogenesis. SREBF1-mediated up-regulation of fatty acid synthesis results in a transient accumulation of lipid droplets and enhancement of fatty acids oxidation through mitochondrial respiration. While this heightened bioenergetic activity is important to sustain melanogenesis, it impairs mitochondria lately, shifting the metabolism towards glycolysis. This recovery phase is accompanied by activation of the NRF2 detoxication pathway. Finally, we show that inhibitors of lipid metabolism can resolve hyperpigmentary conditions in a guinea pig UV-tanning model. Our study reveals rewiring of the metabolic circuit during melanogenesis, and fatty acid metabolism as a potential therapeutic target in a variety of cutaneous diseases manifesting hyperpigmentary phenotype.